A study of the association of HLA DR, DQ, and complement C4 alleles with systemic lupus erythematosus in Iceland - Steinsson, K; Jonsdottir, S; Arason, G J; Kristjansdottir, H; Fossdal, R; Skaftadottir, I; Arnason, A (Annals of the Rheumatic Diseases, 2009)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field OBJECTIVE: To perform an exploratory analysis of the relative contribution of single MHC genes to the pathogenesis of systemic lupus erythematosus (SLE) in a homogenous white population. METHODS: MHC class II alleles and C4 allotypes were determined in 64 SLE patients and in ethnically matched controls. HLA-DR and DQ typing was performed by polymerase chain reaction amplification with sequence specific primers. C4 allotypes were determined by agarose gel electrophoresis. RESULTS: The frequency of C4A*Q0 was significantly higher in patients than in controls (46.9% v 25.3%, p = 0.002). HLA-DRB1, DQA1, and DQB1 alleles in the whole group of SLE patients were not significantly different from those of controls. On the other hand increase in DRB1*03 was observed in the group of patients with C4A*Q0, as compared with patients with other C4A allotypes (p = 0.047). There was no significant correlation between severe and mild disease, as judged by the SLEDAI, and HLADR, DQ alleles and comparing the patients with C4A*Q0 with those with other C4A allotypes there was no significant difference regarding clinical manifestations. CONCLUSION: The results are consistent with the argument that C4A deficiency contributes independently to susceptibility and the pathogenesis of SLE. C4A*Q0 in SLE patients in Iceland shows weaker linkage disequilibrium with DR3 genes than reported in most other white populations and emphasises the role of ethnicity.